The transfer and diffusion of HRM practices within MNCs: lessons learned and future research directions. Issue 1 (2nd January 2017) - Chiang, Flora F. T.; Lemański, Michał K.; Birtch, Thomas A.
Abstract: The transfer and diffusion of human resources management (HRM) practices within the geographically dispersed operations of multinational corporations (MNCs) is receiving heightened attention, in particular because it is believed to significantly influence the performance and competitiveness of MNCs and their subsidiaries. However, as a review of the current body of literature suggests, further work is needed if we are to more fully understand the underlying process through which HRM practices are transferred and diffused or provide more holistic guidance with practitioner relevance. In this article, the authors review and synthesize the extant literature on the transfer and diffusion of HRM practices in the MNC context. Five salient themes or questions that prior research attempts to address are identified and critiqued. A general guiding framework is proposed as are possible avenues for future research.